Restorative Justice in Settlement of Indigenous Based Land Dispute: Study of Mpili Village Donggo District Bima Donggo Regency - Darmawansyah, Darmawansyah; Jainuddin, Jainuddin; Hikmah, Hikmah (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
The study discusses related to Justice Restorative Analysis of the Resolution of Land Disputes through Indigenous. The background of the problem in the study is the resolution of the dispute of land heirs through formal law is considered inadequate in solving the root of the problem thoroughly, because it ignores the social and cultural aspects of the local community. The research method used is an empirical juridical approach with qualitative methods. Data is collected through library studies, in-depth interviews with customary figures, legal experts, and parties involved in heir land disputes. The results of the study showed that the indigenous mechanisms in resolving land disputes generally reflect the restorative principles of justice, namely the restorative principles of social relations, inter-party dialogue, mutual consensus, and resolve oriented towards communal justice and social harmony. Indigenous settlement proved more acceptable by the community of Mpili Village Donggo District Bima because it is participatory, flexible, and rooted in local values. [Penelitian ini membahas terkait dengan Analisis Restoratif Justice terhadap Penyelesaian Sengketa Tanah Waris melalui Adat. Latar belakang permasalahan dalam penelitian ialah penyelesaian sengketa tanah waris melalui hukum formal dianggap tidak memadai dalam menyelesaikan akar permasalahan secara menyeluruh, karena mengabaikan aspek sosial dan budaya masyarakat setempat. Metode penelitian yang digunakan adalah pendekatan yuridis empiris dengan metode kualitatif. Data dikumpulkan melalui studi kepustakaan, wawancara mendalam dengan tokoh adat, ahli hukum, serta pihak-pihak yang terlibat dalam sengketa tanah waris. Hasil penelitian menunjukkan bahwa mekanisme adat dalam menyelesaikan sengketa tanah waris secara umum mencerminkan prinsip-prinsip restoratif justice, yaitu pemulihan hubungan sosial, dialog antar pihak, musyawarah mufakat, serta penyelesaian yang berorientasi pada keadilan komunal dan harmoni sosial. Penyelesaian adat terbukti lebih diterima oleh masyarakat Desa Mpili Kecamatan Donggo Kabupaten Bima karena bersifat partisipatif, fleksibel, dan berakar pada nilai-nilai lokal.]